SOFTWARE SECURITY IS SOFTWARE RELIABILITY. - Lindner, Felix (FX) (Communications of the ACM, 2006)
The article discusses the need for computer hackers, software developers and researchers to collaborate in the naming of computer security bugs and vulnerabilities. The author believes that computer hackers and academic researchers could compliment each other's work if they were able to work together more effectively. He identifies the lack of academic credentials of computer hackers as a problem. He sees the differences in the approaches of computer hackers and institutional computer experts as an impediment to closer collaboration.